2020
DOI: 10.1038/s41419-020-2627-5
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of interleukin-8 and PTEN inactivation promotes the malignant progression of head and neck squamous cell carcinoma via the STAT3 pathway

Abstract: Interleukin-8 (IL-8) expression correlates with poor prognosis in many cancers, including head and neck squamous cell carcinoma (HNSCC), but the underlying mechanism is poorly understood. In this study, we found that overexpression of IL-8 correlated with poor outcome in HNSCC patients. IL-8 significantly increased cellular proliferation, migration, and invasion ability both in vitro and in vivo, which could be blocked by a CXCR1/2 inhibitor. IL-8 promoted the expression of MMP2, MMP9, snail, and vimentin in H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 37 publications
1
30
0
2
Order By: Relevance
“…Similar effects have been found in other cancers—namely, IL-6 has been shown to induce the activation of the EMT program via STAT3 activation in breast cancer [ 54 ] and to play a role in cancer stemness of osteosarcoma cells via STAT3 activation [ 55 ]. Xu et al reported that IL-8 promoted the malignant progression of HNSCC cells via STAT3 phosphorylation [ 56 ]. Therefore, the induction of EMT through the STAT3 signaling pathway, mediated by IL-6 and IL-8, is important to the metastasis of HNSCC, and is associated with poor clinical outcomes [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar effects have been found in other cancers—namely, IL-6 has been shown to induce the activation of the EMT program via STAT3 activation in breast cancer [ 54 ] and to play a role in cancer stemness of osteosarcoma cells via STAT3 activation [ 55 ]. Xu et al reported that IL-8 promoted the malignant progression of HNSCC cells via STAT3 phosphorylation [ 56 ]. Therefore, the induction of EMT through the STAT3 signaling pathway, mediated by IL-6 and IL-8, is important to the metastasis of HNSCC, and is associated with poor clinical outcomes [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, CCL21/CCR7 axis has been shown to promote MMP-9 release, stimulate tumor cell survival, adhesion, invasion, and metastasis in HNSCC [ 134 , 135 , 136 , 137 ]. IL-8 and its receptors CXCR1 and CXCR2 are overexpressed in HNSCC and involved in progression, metastasis, and aggressive tumor phenotype [ 161 , 219 ]. The underlying mechanisms revealed inactivation of PTEN and activation of the STAT3 signaling pathway by IL-8/CXCR1/2 axis in promoting aggressive HNSCC phenotype [ 219 ].…”
Section: Chemokines and Cytokines Promote Aggressive Hnscc Phenotypementioning
confidence: 99%
“…IL-8 and its receptors CXCR1 and CXCR2 are overexpressed in HNSCC and involved in progression, metastasis, and aggressive tumor phenotype [ 161 , 219 ]. The underlying mechanisms revealed inactivation of PTEN and activation of the STAT3 signaling pathway by IL-8/CXCR1/2 axis in promoting aggressive HNSCC phenotype [ 219 ]. In addition to IL-8, migration inhibitory factor (MIF) from tumor cells induces CXCR2-dependent chemotaxis, improved neutrophil survival, and release of CCL4 and MMP-9, helping develop aggressive HNSCC phenotype [ 220 ].…”
Section: Chemokines and Cytokines Promote Aggressive Hnscc Phenotypementioning
confidence: 99%
“…STAT3 and PTEN demonstrate interactions in cancer cells. IL-8 can reduce PTEN expression via phosphorylation to stimulate STAT3 signaling, resulting in enhanced cancer progression [ 161 ]. Furthermore, STAT3 can function as an upstream mediator of PTEN by activating lncRNA cancer susceptibility candidate 9 (CASC9) to diminish PTEN expression, resulting in bladder cancer progression [ 162 ].…”
Section: Microrna and Pten Relationshipmentioning
confidence: 99%